Family Functioning and Psychosocial Factors in a Weight Loss Randomized Controlled Pilot for Black Men. Issue 1 (February 2020) - Alick, Candice L.; Samuel-Hodge, Carmen; Ward, Dianne; Ammerman, Alice; Rini, Christine; Edwards, Christopher L.; Tate, Deborah F.
Abstract : The aim of this study was to explore whether the Together Eating & Activity Matters trial, a spousal support-enhanced randomized control pilot for weight loss among Black men, changed the intended theoretical constructs of family functioning, social support, self-regulation, and self-efficacy. In Together Eating & Activity Matters, 40 Black men were randomized to 2 experimental groups (standard [n = 19]; enhanced [n = 21]). Among the enhanced group, communication and incendiary communication increased and family cohesion and emotional involvement decreased. There were no significant differences between groups on other measures. These results may help explain and document the process of change associated with couples-based interventions in Black men. Lastly, and with this pilot study, we highlight a potentially significant intervention for future research and weight loss in Black men.